PENGALAMAN WANITA PEKERJA SEKSUAL DALAM MENJALANI PROGRAM VOLUNTARY COUNSELING AND TESTING (VCT) HIV/AIDS - Ida Friyanti Sitanggang; Yulia Irvani Dewi; Jumaini Jumaini (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
HIV testing service called Voluntary Counseling and Testing (VCT) is a service that can be accessed easily by WPS, to know their HIV status and their behavioral change in HIV prevention. This study was qualitative research with phenomenology of approach. The purpose of this study was to describe experience of WPS in doing VCT in Jondul Localization. Four participants were selected by purposive sampling method and data were collected by in-depthinterview which completed by field note and analyzed by Colaizzi method. This study identified four major themes: (1) understanding about HIV/AIDS, (2) understanding of VCT (3) hope of keep doing VCT implementation (4) the risks of working as WPS. All of participants got information about HIV/AIDS or sexual transmitted diseases when they did VCT, it was useful to behavioral change and preventive efforts. Through this information, the WPS can knew about her HIV statues, treatment, and feels cared by health workers. Partisipants realized that their work is high risk to infected by HIV/AIDS, so used condom during working and refuse customers that didn’t want to use condom. Beside that, WPS plan to stop working as a preventive efforts. Some hopes from WPS in VCTimplementation, especially for the government that VCT continues to be implemented. The results of this study recommends to WPS for routinely undergo VCT, and recommended to health workers to keep continually preventive efforts by VCT to minimizing the incidence of HIV/AIDS.Keywords: HIV/AIDS, VCT, Women Sexual Workers.